Knowledge appreciates your generosity: exploring a meeting point between knowledge and wisdom. (1st December 2015) - Rooney, David
Abstract : I pay tribute to Don Lamberton in this paper by exploring the importance of generosity in knowledge systems. The purpose of this paper is to show that a range of important dynamics in knowledge systems are enhanced by generosity. I also argue that generosity is one of the meeting points between knowledge and wisdom, and that it should become an important consideration in the knowledge policy development process. It is important that we move knowledge systems closer to wisdom if we are to respond in the best ways to such major global challenges as climate change, a fragile global financial system, the emergence of new technologies, poverty, endemic military and paramilitary conflict, and global food and water security.